2022
DOI: 10.1002/ange.202115331
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Atom‐Substitution Engineered Transition‐Metal Hydroxide Nanofibers with High‐Valence Fe for Efficient Electrochemical Water Oxidation

Abstract: Developing low‐cost electrocatalysts for efficient and robust oxygen evolution reaction (OER) is the key for scalable water electrolysis, for instance, NiFe‐based materials. Decorating NiFe catalysts with other transition metals offers a new path to boost their catalytic activities but often suffers from the low controllability of the electronic structures of the NiFe catalytic centers. Here, we report an interfacial atom‐substitution strategy to synthesize an electrocatalytic oxygen‐evolving NiFeV nanofiber t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…17–19 Hence, numerous strategies have been developed to further optimize the electrocatalytic performance of NiFe-LDH, including morphology modulation, anion exchange or intercalation, heteroatom doping or substitution, and defect engineering. 20–25 Liu et al synthesized oxygen vacancy-rich hierarchical NiFe-LDH microtubes assembled using two-dimensional nanosheets via a template-assisted strategy as a way to increase the number of catalytically active sites. 26 Wu et al reported a surface strategy to manipulate the coordinatively unsaturated metal sites of NiFe-LDH to enhance the OER activity of the catalyst by using an optimized amount of ammonium fluoride (NH 4 F) as a metal-complexing agent.…”
Section: Introductionmentioning
confidence: 99%
“…17–19 Hence, numerous strategies have been developed to further optimize the electrocatalytic performance of NiFe-LDH, including morphology modulation, anion exchange or intercalation, heteroatom doping or substitution, and defect engineering. 20–25 Liu et al synthesized oxygen vacancy-rich hierarchical NiFe-LDH microtubes assembled using two-dimensional nanosheets via a template-assisted strategy as a way to increase the number of catalytically active sites. 26 Wu et al reported a surface strategy to manipulate the coordinatively unsaturated metal sites of NiFe-LDH to enhance the OER activity of the catalyst by using an optimized amount of ammonium fluoride (NH 4 F) as a metal-complexing agent.…”
Section: Introductionmentioning
confidence: 99%
“…Solar and wind energy are diffuse and intermittent. Efficient, high-capacity and output- storage methods are needed to transition to carbon-zero energy production. , Electrochemical water splitting to form hydrogen and oxygen is a promising approach. , Unfortunately, the electrooxidation of water to oxygen, called the oxygen evolution reaction (OER), is slow, and it remains a significant challenge to develop low-cost, stable OER electrodes with low overpotentials and loadings at high current densities. , Further, electrode preparations must be straightforward and utilize abundant starting materials for widespread, large-scale utilization …”
Section: Introductionmentioning
confidence: 99%
“…5,6 Further, electrode preparations must be straightforward and utilize abundant starting materials for widespread, large-scale utilization. 7 Nonprecious metal OER electrocatalysts help fulfill these requirements. The reported systems are typically more active in base.…”
Section: ■ Introductionmentioning
confidence: 99%